Effects of type of tapering on anaerobic capacity in young basketball players - Lira, Hugo Augusto Alvares da Silva (2017)
The aim of this study was to analyze the effect of the type of tapering on anaerobic capacity in male young basketball players. This was an experimental research with 12 weeks, developed with 47 basketball players, randomly divided into three groups: linear tapering (LG), tapering by step (SG) and control group (CG). All groups participated of the same planning training until the last three weeks of periodization (the tapering phase). Only the CG did not perform tapering. Anaerobic Running Speed Test was carried in the last week of each mesocycle to assess the anaerobic capacity. The findings revealed that anaerobic capacity attenuated from the competitive to tapering phase in LG (p= .01) and SG (p= .01), which was not verified for the CG (p= .29). Significant difference of anaerobic capacity was found between LG and CG (p= .01), SG and CG (p= .01) and between LG and SG (p= .04) in the tapering phase. It was concluded that the tapering strategies were efficient to maximize anaerobic capacity in young basketball players, although linear tapering strategy has been revealed the best strategy for improvement the anaerobic capacity.